Wczesna edukacja i opieka nad małym dzieckiem jako wyzwanie dla systemu edukacji - Czub, Magdalena; Appelt, Karolina (Wydawnictwo Naukowe UAM, 2013)
This paper addresses the problem of supporting the development of infants and young children in the context of the challenges posed by the organization of the state system. Considering the importance of the fi rst years of life for future development, current social policy and education in Europe and around the world puts a strong emphasis on systemic and integrated approach to early childhood education and care, based on scientifi c evidence justifying the selection of a specifi c social and educational solutions. The implementation of this idea requires both the defi nition of the most important aspects of the development, requiring special support in the early stages of child development and system design early care and education with regard to the resulting knowledge. The following analysis is an attempt to identify the most important factors and social conditions indispensable to fulfi ll both the universal and the individual needs of the child in the context of the challenges they pose for organizers of the system of early childhood education and care.
Early childhood education and care: a challenge for the educational system
Keywords: infancy; early childhood; care; education; early childhood education and care system